Cryptic invasion suggested by a cytogeographic analysis of the halophytic Puccinellia distans complex (Poaceae) in Central Europe - Kúr, Pavel; Gregor, Thomas; Jandová, Michaela; Mesterházy, Attila; Paule, Juraj; Píšová, Soňa; Šemberová, Kristýna; Koutecký, Petr; Ducháček, Michal; Schneeweiss, Gerald M. (Frontiers in Plant Science, 2023)
Despite the wealth of studies dealing with the invasions of alien plants, invasions of alien genotypes of native species (cryptic invasions) have been vastly neglected. The impact of cryptic invasions on the biodiversity of plant communities can, however, be significant. Inland saline habitats and halophytes (i.e., salt-tolerant plant species) are especially threatened by this phenomenon as they inhabit fragmented remnants of largely destroyed habitats, but at the same time some of these halophytic species are rapidly spreading along salt-treated roads. To study potential cryptic invasion of halophytes, the patterns of genome size and ploidy variation in the Puccinellia distans complex (Poaceae), the most rapidly spreading roadside halophyte in Central Europe, were investigated. DNA flow cytometry with confirmatory chromosome counts were employed to assess ploidy levels of 1414 individuals from 133 populations of the P. distans complex. In addition, climatic niche modelling was used to predict the distributions of selected cytotypes. Eight groups differing in ploidy level and/or genome size were discovered, one diploid (2x; 2n = 14), two tetraploid (4xA, 4xB; 2n = 28), one pentaploid (5x; 2n = 35), three hexaploid (6xA, 6xB, 6xC; 2n = 42), and one heptaploid (7x; 2n = 49). The hexaploids (mostly the 6xC cytotype) were widespread through the study area, spreading intensively in both anthropogenic and natural habitats and probably hybridizing with the natural habitat dwelling tetraploids. In contrast, the non-hexaploid cytotypes rarely spread and were predominantly confined to natural habitats. The extensive spread of the hexaploid cytotypes along roadsides has most likely facilitated their incursion into natural habitats. The colonization of new natural habitats by the hexaploids may pose a threat to the indigenous Puccinellia populations by compromising their genetic integrity and/or their outcompeting.